1994
DOI: 10.1111/j.1365-2885.1994.tb00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of ciprofloxacin following intravenous administration in dogs

Abstract: The pharmacokinetics of ciprofloxacin (CIP) following intravenous administration in dogs have been investigated. The drug was administered at three doses (2.5, 5 and 10 mg/kg body weight) and was assayed in biological fluid samples (plasma and urine) by an HPLC method. The plasma concentration-time curves were best described by a two-compartment open pharmacokinetic model. The drug was widely distributed (Vd(area) almost 3 l/kg), being distributed in the dog more rapidly than in other species (t1/2(lambda 1) 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 29 publications
6
22
1
Order By: Relevance
“…Upon multiple dosing, ciprofloxacin, enoxacin and other fluoroquinolones have shown an increase in the t 1/2 and increased V d from the first dose (Chang et al, 1988;Nix and Schentag, 1988); however, this phenomenon was not observed for norfloxacin in dogs using a dosage regimen of 5 mg/ kg every 12 h for 14 days (Brown et al, 1990) nor for ciprofloxacin in other studies (Höffler et al, 1984;Drusano et al, 1986) nor in dogs (Abadía et al, 1994b). The area under the concentration time curve normalized to a 1 mg/kg dose decreased as the dose of norfloxacin increased from 5 mg/kg to 20 mg/kg in healthy dogs (Brown et al, 1990).…”
Section: Pharmacokineticsmentioning
confidence: 85%
See 2 more Smart Citations
“…Upon multiple dosing, ciprofloxacin, enoxacin and other fluoroquinolones have shown an increase in the t 1/2 and increased V d from the first dose (Chang et al, 1988;Nix and Schentag, 1988); however, this phenomenon was not observed for norfloxacin in dogs using a dosage regimen of 5 mg/ kg every 12 h for 14 days (Brown et al, 1990) nor for ciprofloxacin in other studies (Höffler et al, 1984;Drusano et al, 1986) nor in dogs (Abadía et al, 1994b). The area under the concentration time curve normalized to a 1 mg/kg dose decreased as the dose of norfloxacin increased from 5 mg/kg to 20 mg/kg in healthy dogs (Brown et al, 1990).…”
Section: Pharmacokineticsmentioning
confidence: 85%
“…or IV) in calves (Grimshaw et al, 1990b;, 5.4 ± 0.9 h for enrofloxacin in calves (Sheer, 1987), 2-4 h for ciprofloxacin in dogs (Abadía et al, 1994b) and horses (Dowling et al, 1995), 3.6 h for norfloxacin (IV) in dogs (Brown et al, 1990), and 3 hours for enrofloxacin in laboratory Beagles compared to 5.0 ± 1.0 h in canine clinical patients. The interspecies differences are important: enrofloxacin has an elimination half-life of 7.3, 1.4, 1.2, 2.1 and 3.3 hours in the chicken, turkey, calf, dog and horse, respectively (VanCutsem et al, 1990).…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, the reported values of elimination half-life of ciprofloxacin in dog were 8-10 hr (Boothe et al 2002), 4.81 hours (Abadia et al 1995) after oral administration @ 10-20 mg/kg of drug and 2.15-3.0 hours (Abadia et al 1994) after oral administration @ 5-10 mg/kg of drug. While elimination half-life of ciprofloxacin as reported in goats is 1.38 hours (Rao et al 2001).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, two compartment open model was selected to explain the disposition kinetics of ciprofloxacin in present study. Similarly, the disposition kinetics of ciprofloxacin was best modeled using a two-compartment open model in dogs (Abadia et al 1994). Any how, plasma concentrations of ciprofloxacin were best fitted by one compartment open model in dogs (Abadia et al 1995) and by non compartmental analysis in dogs (Boothe et al 2002).…”
Section: Discussionmentioning
confidence: 99%